Targeting immuno-metabolism to improve anti-cancer therapies. (1st February 2018) - Beezhold, Kevin; Byersdorfer, Craig A.
Abstract: The immunology community has made significant strides in recent years in using the immune system to target and eliminate cancer. Therapies such as hematopoietic stem cell transplantation (HSCT) are the standard of care treatment for several malignancies, while therapies incorporating chimeric antigen receptor (CAR) T cells or checkpoint molecule blockade have been revolutionary. However, these approaches are not optimal for all cancers and in some cases, have failed outright. The greatest obstacle to making these therapies more effective may be rooted in one of the most basic concepts of cell biology, metabolism. Research over the last decade has revealed that T cell proliferation and differentiation is intimately linked to robust changes in metabolic activity, delineation of which may provide ways to manipulate the immuno-oncologic responses to our advantage. Here, we provide a basic overview of T cell metabolism, discuss what is known about metabolic regulation of T cells during allogeneic HSCT, point to evidence on the importance of T cell metabolism during CAR T cell and solid tumor therapies, and speculate about the role for compounds that might have dual-action on both immune cells and tumor cells simultaneously. Highlights: Discuss our current understanding of T cell metabolism during activation and GVHD. Review recent progress in understanding the metabolism of TIL and CAR T cells. Discuss metabolic approaches to target cancer cells and enhance immune function.